Association Between Social Capital and Anxiety Among Older Adults in China: A Cross-Sectional Study - Meng L; Li P; Ye L; He Y; Zhong J (Psychology Research and Behavior Management)
Lingyao Meng,1,2 Pan Li,1,2,* Lijuan Ye,3,* Yongmei He,1 Jiaming Zhong4 1School of Nursing, XiangNan University, Chenzhou, People’s Republic of China; 2College of Nursing and Allied Health Sciences, St. Paul University Manila, Manila, Philippine; 3School of Chemical and Environmental Sciences, XiangNan University, Chenzhou, People’s Republic of China; 4School of Economics and Management, XiangNan University, Chenzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pan Li, School of Nursing, XiangNan University, Chenzhou, People’s Republic of China, Tel +86 17773560292, Email lipan1020@xnu.edu.cn Lijuan Ye, School of Chemical and Environmental Sciences, XiangNan University, Chenzhou, People’s Republic of China, Tel +86 15173505843, Email yelijuan68116@163.comPurpose: Social capital is one key determinant of older adults’ mental health, yet its link with various demographic variables and anxiety among older adults in China remains underreported. This study investigated whether there is an interactive effect of social capital and demographic factors on anxiety among Chinese older adults.Methods: A sample of 5115 Chinese older adults (≥ 60 years old) was extracted from cross-sectional survey data in the 2018 Chinese Longitudinal Health and Longevity Study (CLHLS). Data on demographic characteristics, social capital, and anxiety were collected. Binary logistic regression models and a classification and regression tree model (CART) were performed to assess the association between social capital and anxiety.Results: The finding of this study showed that the prevalence of anxiety among Chinese older adults was 13.04% (667/5115), subjects who were female (OR = 1.649; 95% CI: 1.336– 2.036), with medium-level of annual family income (OR = 0.598; 95% CI: 0.476– 0.751), with reporting 1– 2 diseases (OR = 1.743; 95% CI: 1.322– 2.298), with medium-level of interpersonal trust (OR = 0.668; 95% CI: 0.533– 0.837), social participation (OR = 0.521; 95% CI: 0.390– 0.696), social support (OR = 0.431; 95% CI: 0.264– 0.703) were at a lesser risk of developing anxiety. We also noted the interactive relationship of social capital associated with anxiety, which indicated that special attention and efforts should be paid to older adults who were females, with lower interpersonal trust, annual family income, and lower social participation to maintain sound mental status.Conclusion: Our findings indicate that social capital is associated with anxiety in Chinese older adults. This implies that social capital, especially in terms of gender, annual family income, interpersonal trust, and social participation may be significant for alleviating anxiety in later life.Keywords: anxiety, interpersonal trust, social participation, social support, older adults, decision tree